(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Because of the increasing interest in nano composites, the molecular characterization ofthese materials is important to understand the new materials and the property of the new material. Thespectroscopic technicians who provide information are immensely indispensable to thecharacterization of polymers, fillers and compounds at the molecular level. Selected examples forfluorescence spectroscopy, the use of magnetic laughter nuclear (NMR) in solid state, infrared andRaman spectroscopy, the potential of these techniques for surface load analysis, the state of chargedistribution in the matrix or host, and the degree of interaction with the polymer and dynamics.